ANALISIS RANTAI NILAI (VALUE CHAIN) UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI CEMENT RETARDER - PUTRI WULANDARI, OKTAVIA (Jurnal Akuntansi AKUNESA, 2017)
This study aims to identify the activities of the firm?s value chain and cost driver of Cement Retarder. Value chain analysis can help the firm?s to improve cost efficiency. This study used a descriptive qualitative method in analyzing firm?s value chain activities. This study began by identifying the activities of the value chain by classifying each activity into the main activities and supporting activities. Followed by identification of the cost driver on each value activity. Based on the results of the identification and then carried out the analysis. The result of the study indicates that based on calculations through value chain analysis and cost driver it is known that there is an overcosting on overhead cost per ton of Cement Retarder. The difference is due to differences in the accuracy of charging costs that may the result in inaccuracy of allocation costs.